2013
DOI: 10.5489/cuaj.1153
|View full text |Cite
|
Sign up to set email alerts
|

Malignant lymphoma of the testis: a study of 12 cases

Abstract: Introduction: Testicular lymphoma is a rare and deadly disease representing 1% to 2% of all non-Hodgkin lymphomas (NHLs) and approximately 5% of all testicular neoplasms. Our objective is this study was to identify the presenting signs and symptoms, treatment and outcome of patients with testicular lymphoma diagnosed at our institution from 1992 to 2005, and to identify any differences in survival based on Ann Arbor Stage and International Prognostic Index (IPI). Methods:A retrospective chart review was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 22 publications
4
43
1
6
Order By: Relevance
“…17%, respectively, which was comparable with the results of pre vious reports in which the median OS period of limited staged disease ranged from 5.3 years to 6.3 years and the 5 year OS rate ranged from 58% to 85%. 7,8,12,14 The most favorable treatment result was reported by Vitolo et al, 12 in which all patients underwent a treatment protocol comprising orchidectomy, R CHOP, CNS pro phylaxis, and contralateral testis irradiation. In comparison with the results of Vitolo et al, 12 our patients received a different treat ment protocol, and many patients did not receive complete R CHOP chemotherapy regimens, prophylactic radiotherapy, or intrathecal chemotherapy.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…17%, respectively, which was comparable with the results of pre vious reports in which the median OS period of limited staged disease ranged from 5.3 years to 6.3 years and the 5 year OS rate ranged from 58% to 85%. 7,8,12,14 The most favorable treatment result was reported by Vitolo et al, 12 in which all patients underwent a treatment protocol comprising orchidectomy, R CHOP, CNS pro phylaxis, and contralateral testis irradiation. In comparison with the results of Vitolo et al, 12 our patients received a different treat ment protocol, and many patients did not receive complete R CHOP chemotherapy regimens, prophylactic radiotherapy, or intrathecal chemotherapy.…”
Section: Discussionmentioning
confidence: 88%
“…The clinical characteristics of the patients in this study were similar to those previously reported. 1,2,4,5,7,8,11,13,14 In addition to old age, the majority of patients presented with uni lateral stages IeII lymphoma and DLBCL. These observations sug gest that the characteristics of PTL appear to be similar worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A TNHL-lel diagnosztizált betegek leggyakoribb panasza az első orvos-beteg találkozás alkalmával az egyik vagy mindkét here duzzanata, másodsorban ismeretlen okú testtömegcsökkenést, továbbá lázat és éjszakai izzadást említenek [4]. A daganat irreguláris, hipodenz inhomogenitást mutat az ultrahangképen, amely általában már a kezdetekkor felveti a malignitás gyanúját.…”
unclassified